Nonlinear continuum mechanics for finite element analysis - Bonet, Javier, 1961-; Wood, Richard D., 1943-; Cambridge eBooks (Cambridge : Cambridge University Press, 2008)
Designing engineering components that make optimal use of materials requires consideration of the nonlinear characteristics associated with both manufacturing and working environments. The modeling of these characteristics can only be done through numerical formulation and simulation, and this requires an understanding of both the theoretical background and associated computer solution techniques. By presenting both nonlinear continuum analysis and associated finite element techniques under one roof, Bonet and Wood provide, in this edition of this successful text, a complete, clear, and unified treatment of these important subjects. New chapters dealing with hyperelastic plastic behavior are included, and the authors have thoroughly updated the FLagSHyP program, freely accessible at www.flagshyp.com. Worked examples and exercises complete each chapter, making the text an essential resource for postgraduates studying nonlinear continuum mechanics. It is also ideal for those in industry requiring an appreciation of the way in which their computer simulation programs work.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Materials -- Mathematical models; Continuum mechanics; Nonlinear mechanics; Finite element method; Electronic books